Sources on historical newspapers in Rijeka (1813-1818) (Libellarium: journal for research in the field of information and related sciences, 2011)
The lack of a holistic overview of the Rijeka historical newspapers from the beginnings of newspaper printing in 1813 to 1818 has caused many problems in conducting research on the history of Rijeka, both when it comes to individual events and the general context. This situation brought about the need to conduct a comparative analysis of available resources on historical newspapers in Rijeka and make a systematic overview of all titles published in that period. The various sources consulted during research (papers, mostly bibliographies, which deal with the historical newspapers in Rijeka) were analyzed systematically and comparatively, and the data on each title, as well as the titles themselves had to be verified, as they were not transparently stated in all sources, with the aim of making a list of newspapers by definition and features. This provided a platform for future research and cleared some ground for the investigation of historical newspapers in Rijeka.This research provides new, amended or altered data about the title, masthead, or frequency of publication for particular papers (which would often change over the years), which are crucial from the book trade as well as research perspectives. The research is not deemed final and concluded - the need for further examination of data on particular historical newspapers is underlined, bearing in mind that the last systematic research was conducted 50 years ago.
Keywords: historical newspapers in Rijeka; research on historical newspapers; old or historical newspapers; Croatian newspaper records